Upaya Pencegahan Hipertensi Usia Produktif dengan Media Booklet GEBRAK SEHATI di Wilayah Kerja UPTD Puskesmas Tapos - Nina Nina; Widya Rachma Pramudita; Fadhillah Fathan; Alicia Hera Ramadhani; Rizky Aranda; Miranti Blandin Laleda; Muhammad Gian Purnama (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
The prevalence of hypertension in Indonesia continues to rise, affecting not only the elderly but also young adults. Preliminary studies indicate that the low public interest in health promotion is a major factor contributing to the increased risk of hypertension among individuals in their productive years. Based on the results of Field Study Practice (PBL) stages 1 and 2, this issue stems from the use of less engaging media. To address this problem, a health education program titled Gerakan Berantas Hipertensi untuk Usia Produktif (GEBRAK SEHATI) was conducted on July 31, 2024, in the service area of UPTD Puskesmas Tapos, with 18 participants. The program aimed to increase public interest and participation in preventing and managing hypertension. The method employed was Focus Group Discussion (FGD) using flip charts and booklet dissemination. The results showed a significant improvement in participants' understanding, with the average pre-test score of 80 increasing to 90 in the post-test. This improvement indicates that the GEBRAK SEHATI program successfully enhanced public awareness and understanding of hypertension. It is hoped that with continued and effective educational methods, this program will further improve public interest in health promotion, thereby reducing the prevalence of hypertension among productive-age individuals.